Influence of crude oil pollution on the content and electrophoretic spectrum of proteins in Carex hirta plants at the initial stages of vegetative development - BunіoL. V.; Tsvilynyuk, O. M. (Regulatory Mechanisms in Biosystems, 2021)
The role of proteins in the general adaptive response of Carex hirta plants to soil pollution by crude oil has been studied. It was established that a possible element of the process of adaptation of C. hirta plants to combined stress – conditions of soil polluted by crude oil – may be the synthesis of stress proteins – high molecular weight of more than 60 kD and low molecular weight, not exceeding 22–45 kD. The synthesis of all 5 HSP families was detected in the leaves and rhizomes, and only sHSP (starting from Mr 32 kD), Hsp 60 and Hsp 100 proteins were synthesized in the roots under the influence of crude oil pollution. The development of C. hirta adaptation syndrome under the influence of crude oil pollution of the soil was promoted by enhanced synthesis of proteins with Mr 85, 77, 64, 60 and 27 kD in the leaves, 118 and 41 kD in the rhizomes and proteins with Mr 105, 53, 50 and 43 kD in the roots of the plants. The decrease in the amount of proteins with Mr 91, 45, 28 kD in the leaves, proteins with Mr 85, 76 and 23 kD in rhizomes and proteins with Mr 64 and 39 in the roots of C. hirta plants under conditions of crude oil polluted soil could be a consequence of inhibition of synthesis or degradation of protein molecules providing the required level of low molecular weight protective compounds in cells. The root system and rhizomes of C. hirta plants undergo a greater crude oil load, which leads to increased protein synthesis in these organs and decreased in the leaves, correspondingly. However, a decrease in protein content in the leaves may indicate their outflow in the roots and rhizomes. Сrude oil contaminated soil as a polycomponent stressor accelerated the aging of leaves of C. hirta plants, which could be caused by increased synthesis of ABA. ABA in its turn induced the synthesis of leaf-specific protein with Mr 27 kD. These proteins bind significant amounts of water with their hydrate shells maintaining the high water holding capacity of the cytoplasm under drought conditions. ABA inhibits the mRNA synthesis and their corresponding proteins, which are characteristic under normal conditions, and induces the expression of genes and, consequently, the synthesis of specific proteins including 27 kD protein. By stimulating the expression of individual genes and the synthesis of new polypeptides, ABA promotes the formation of protective reactions and increases the resistance of plants to crude oil pollution.